2012
DOI: 10.1111/all.12081
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and newborn vitamin D status and its impact on food allergy development in the German LINA cohort study

Abstract: Our study demonstrates that high vitamin D levels in pregnancy and at birth may contribute to a higher risk for food allergy and therefore argues against vitamin D supplement to protect against allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
177
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(193 citation statements)
references
References 38 publications
(47 reference statements)
7
177
1
8
Order By: Relevance
“…38,45 Mullins et al, 52 though, found a decrease in peanut allergy in the third quartile (75-99.9 nmol/L) compared with the reference second quartile (50-74.9 nmol/L) but found no significant differences between the first or fourth quartiles compared with the reference quartile. The study by Weisse et al 50 showed a positive associ- …”
Section: Allergic Diseasementioning
confidence: 90%
See 2 more Smart Citations
“…38,45 Mullins et al, 52 though, found a decrease in peanut allergy in the third quartile (75-99.9 nmol/L) compared with the reference second quartile (50-74.9 nmol/L) but found no significant differences between the first or fourth quartiles compared with the reference quartile. The study by Weisse et al 50 showed a positive associ- …”
Section: Allergic Diseasementioning
confidence: 90%
“…Of the 5 studies that looked at regulatory T cells in cord blood, 3 found no associations. 28,62,63 Vijayendra Chary et al 64 found a positive relationship between cord blood 25(OH)D concentrations and regulatory T cell percentages, while Weisse et al 50 found a negative relationship with cord blood 25(OH)D, but not with maternal 25(OH)D as an exposure. Guven et al 62 and Romero et al 63 looked at a variety of other data points related to cord blood lymphocytes, focusing on T-helper cells, and found no correlation with cord blood 25(OH)D.…”
Section: Infectious Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies Vitamin D deficiency was associated with higher levels of IgE sensitization in children and adolescents (SHARIEF et al, 2011). However later studies demonstrated that high vitamin D levels in pregnancy and at birth may contribute to a higher risk for food allergy and therefore argues against vitamin D supplementation to protect against allergy (WEISSE et al, 2013).…”
Section: New Challenges and Futurementioning
confidence: 99%
“…On one hand, allergies increased coinciding with vitamin D supplementation intervention programs to prevent rickets in childhood [32], and increased risk for asthma and food allergies has been reported among children receiving early vitamin supplementation [33]. In a recent German cohort study, it has been described that higher maternal 25(OH)D 3 results in a higher risk of food allergy sensitization at 2 years of age [34]. On the other hand, the vitamin D deficiency (VDD) hypothesis argues that inadequate vitamin D is responsible for the increase in allergic diseases.…”
mentioning
confidence: 99%